Community forestry, labor migration and agrarian change in a Nepali village: 1980 to 2010. Issue 3 (19th March 2018) - Fox, Jefferson
Abstract : This paper follows forest conditions, agricultural practices, and livelihoods in a Nepali village between 1980 and 2010. A survey was administered to all village households in 1980, 1990 and 2010; semi-structured interviews were also conducted. Tree species frequency, density and dominance were determined for eight forest patches during each survey. Over this period the population of the village remained stable; the number of children decreased, and the number of people over 50 increased. Famers keep significantly fewer livestock, and have become less dependent on farming and more engaged in commercial activities. In 1980 the number of out-migrants was so few that they were not recorded; by 2010, 29 percent of the adult male population was engaged in migration. Nepal initiated an acclaimed Community Forestry program in the early 1990s; by 2010 about half the village's forests showed improved tree density and size. Contrary to expectations and published literature, the study found that forest conditions in half of the village's forests were not improved; and while livelihoods appeared to be better in 2010 than in 1980, they are not more secure as they are increasingly dependent on remittance incomes and hence at the whims of the international labor market.